On the dynamics of inflation persistence around the world - Antonio E. Noriega; Manuel Ramos-Francia (Banco de México, 2009)
We study the dynamics of inflation persistence in 45 countries for the period 1960-2008. We use a nonparametric unit root test robust to nonlinearities, error distributions, structural breaks and outliers, many of them typical features of inflation data, and a test for multiple changes in persistence, which decomposes the sample information between adjacent I(0) and I(1) periods. We find that (1) With very few exceptions, inflation around the world rejects a unit root, (2) for several countries there is evidence of significant changes in persistence, (3) bursts and drops in the level of inflation and in inflation persistence tend to coincide, (4) these drops occurred during 'the Great Moderation' and during the adoption of inflation targeting. We conclude that inflation is characterized by either a stationary behaviour throughout the sample, or by switches of the type I(0)-I(1)-I(0). For all countries in our sample, any indication of nonstationarity seems to be temporary.
Keywords: C12; C22; E31; E52; E58; 330; Inflation; Multiple persistence change; Stationarity; Unit root tests; Unknown direction of change; Monetary policy; Inflation; Geldpolitik; Unit Root Test; Welt